(untitled) (BIRDEM Medical Journal, 2019)
Background: Acute pancreatitis (AP) is characterized by a spectrum of symptoms, ranging from a local inflammatory process to the more severe form (acute necrotizing pancreatitis) which is associated with a systemic inflammatory response. The overall mortality rate of AP is between 5% and 15%, reaching 30 % in severe acute pancreatitis (SAP). Early optimized care may improve prognosis in patients with the most severe forms but it remains a challenge to identify these poor prognosis cases specially in the first 48 hours. The objective of our study is to evaluate the efficacy of serum D-dimer in the prediction of severity and outcome of acute pancreatitis. Methods: This prospective and observational study was conducted in the Department of Gastrointestinal, Hepatobiliary and Pancreatic Disorders (GHPD), BIRDEM General Hospital, Dhaka, Bangladesh from January, 2016 to September, 2017. Patients with acute pancreatitis admitted to Department of GHPD of BIRDEM General Hospital, Dhaka, were included in this study. Purposive type of non probability sampling technique was applied to enroll the patients. A predesigned structured questionnaire was used for recording the necessary information. Patients admitted with abdominal pain and fulfilling the diagnostic criteria of acute pancreatitis by clinical history, physical examination, biochemical tests and different imaging modalities and patients aged more than 18 years were included in this study. The patients were followed up on day 1, day 3 of admission and on the day before discharge. Results: Total 87 patients with acute pancreatitis, who fulfilled the inclusion criteria, were included in this study. This study found that 53(61.0%) had mild acute pancreatitis, 27(31.0%) patients had moderately severe acute pancreatitis and 7(8.0%) patients had severe acute pancreatitis. The mean serum D-dimer at day 1 of patients with mild disease was 2.31± 1.82(mean±SD) μg/ml, in patients with moderately severe disease was 4.67± 2.02(mean±SD) μg/ml and in severe acute pancreatitis it was 10.11±3.11 (mean±SD) μg/ml. The difference among the groups were statistically significant (p<0.001). The mean serum D-dimer at day 3 of patients with mild disease was 0.8±0.51 (mean±SD) μg/ml, in patients with moderately severe disease was 1.86±2.22 (mean± SD) μg/ml and in severe acute pancreatitis it was 3.62±1.9 (mean±SD) μg/ml. The difference among the groups were statistically significant (p<0.001). Thus serum D-dimer could predict disease severity early in the course of disease successfully. In the present study 55(63.2%) patients did not develop any kind of complications and serum D-dimer level at day 1 and day 3 were 2.4±1.73 and 0.81±0.49 respectively. On the other hand 32 (36.8%) patients developed complications and serum D-dimer level at day 1 and day 3 were 5.86±3.5 and 2.31±2.3 respectively. The difference among the groups were statistically significant (p<0.001).That reveals serum D-dimer is a predictor of outcome of acute pancreatitis. Sensitivity, specificity and accuracy was 77.8%, 76.5% and 77.0% respectively at day 1 (cut off value e”3.3 μg/ml) and it was 73.5%, 77.4% and 75.9% respectively at day 3 (cut off value e”1.05 μg/ml) in prediction outcome of AP. Conclusion: The difference of serum D-dimer levels between mild, moderately severe and severe acute pancreatitis was statistically significant and it was also higher in patients who developed complications following acute pancreatitis than those without complications. This simple, feasible and reproducible marker can be used in clinical practice to improve the early management of acute pancreatitis. Birdem Med J 2019; 9(1): 44-54